Anaerobic power as a determinant of performance in elite kayaking: the interplay between aerobic capacity and lactate accumulation - Mika, T.; Sekera, J.; Bolek, E.; Novakova, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Performance in elite kayaking is influenced by a complex interplay between aerobic and anaerobic physiological capacities. This study focused on the specific roles of anaerobic power, demonstrated by peak power (PP) and mean power (MP), in relation to blood lactate concentration and aerobic capacity, measured by VO2max. Kayakers competing at national (Nat) and international (Int) level were assessed. METHODS: A cross-sectional analysis was conducted on 25 male elite kayakers (23 years ± 4 years) stratified into performance levels. Athletes underwent a spiroergometric test to determine VO2max and a Wingate test to measure anaerobic power (PP and MP). Lactate levels were obtained at the seventh minute post-exercise. Descriptive statistics, normality distribution Shapiro Wilk test and for homogeneity of variance Levenes test, Pearson correlation, T- test for independent variables and regression analyses were used to identify key performance determinants. RESULTS: A comparative analysis of kayaking performance metrics revealed that international-level kayakers (Int) demonstrated significantly higher Peak Power (PP), with mean values of 10.43 W/kg, compared to 9.69 W/kg for national-level athletes (Nat) (t-statistic: -2.83, p-value: 0.0096). Mean Power (MP) also tended to be higher in the international group, averaging 7.71 W/kg, in contrast to 7.36 W/kg for the national group, though this difference did not reach statistical significance (t-statistic: -1.40, p-value: 0.1746). No significant differences were observed in Maximal Oxygen Uptake (VO2max), with the international group averaging 59.48 ml/min/kg and the national group 61.70 ml/min/kg (t-statistic: 0.76, p-value: 0.4595). Lactic Acid Maximum (LA max) levels were slightly higher for international competitors, averaging 12.21 mmol/L, compared to 11.38 mmol/L for their national counterparts (t-statistic: -0.90, p-value: 0.3786). Moreover, a significant correlation was found between MP and lactate (r = 0.57, p-value: 0.0028), and a negative correlation was observed between lactate levels and VO2max (r = -0.66, p < 0.05). These findings underscore the importance of anaerobic power in the high-performance profile. CONCLUSION: Our findings suggest that while aerobic capacity provides a fundamental foundation for kayaking performance, the ability to generate and sustain high-intensity anaerobic power, as evidenced by higher peak power and post-exercise lactate levels, is a more significant determinant of success at the highest competitive levels. These insights underscore the importance of tailored training programs that focus on enhancing anaerobic power outputs to improve performance among elite kayakers.